2021
DOI: 10.3390/foods10071580
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic Supplementation Improves Obesity Index and Metabolic Biomarkers in Thai Obese Adults: A Randomized Clinical Trial

Abstract: The cluster of metabolic disorders includes obesity, dyslipidemia, hypertension, and glucose intolerance, increasing the risk of developing cardiovascular diseases and type 2 diabetes. Evolving proofs suggest an essential role of microbiota in human health and disease, including digestion, energy and glucose metabolism, immunomodulation, and brain function. The frequency of overweight is increasing, and the main causes for this are highly processed foods and less active lifestyles. Research is underway to unra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 67 publications
1
46
0
Order By: Relevance
“…In contrast, IgA levels were increased in human subjects significantly. These results suggested that synbiotic intervention could improve obesity-associated biomarkers [17].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In contrast, IgA levels were increased in human subjects significantly. These results suggested that synbiotic intervention could improve obesity-associated biomarkers [17].…”
Section: Discussionmentioning
confidence: 82%
“…The supplementation of L. paracasei HII01 increased the levels of short-chain fatty acids in obese, hypercholesterolemic, and diabetic human subjects [17,37]. 5-HIAA and QA/5-HIAA ratio was not significantly affected by the supplementation of L. paracasei HII01, B. breve, B. longum, inulin, and fructooligosaccharide.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Among the changes seen, both inflammatory and oxidative stress biomarkers improved with the symbiotic supplement. [182] Bifidobacterium longum and the prebiotic, galacto-oligosaccharide A study in mice found that this orally administered symbiotic combination protected against UVB-photoaging of skin. [183] Weissella confusa CGMCC 19,30 A study in the bacterial infection C. elegans model found that this orallyadministered probiotic increased lifespan, improved immunity, and reduced oxidative stress [184] Lactobacillus paracasei GKS6 and Bifidobacterium lactis GKK2 were examined independently.…”
Section: The Immunological Epigenetic Clock Of the Microimmunosomementioning
confidence: 99%